The Effectiveness ofUsing the Mentimeter Application on the Learning Outcomes of Seventh-Grade Students inScience at SMP Negeri 1 Panca Rijang - Nurul Fitrah; Usman M; Muhammad Takdir (Universitas Muhammadiyah Enrekang, 2026)
wew